Improvement of learning result in mathematics subject of speeding material by using “make a match” method in the fifth grade of elementary students in the second semester - Suwito, Suwito (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research was caused by the low of students’ understanding of Mathematics subject which was resulted in the low of students learning result. It was seen from the score of test result (KKM) was less 50% of all. This research aims: 1) To improve the quality of the teaching learning process in the classroom. 2) To improve the student learning result in Mathematic subjects. This research was belonged to Classroom Action Research at SDN 3 Gunting. Its subject was the fifth-grade students of SDN 3 Gunting. There were 4 steps in this research, such as: planning, acting, observing, and reflecting. The conclusion was the improvement of learning result in Mathematic subject by using Make a Match in the fifth-grade students in the second semester of SDN 3 Gunting. It was proven by the improvement learning result of Mathematic subject from 6 students (29%) to 20 students (95%)